UTILIZATION OF TUBIFEX WORMS AS NATURAL FEED FOR GROWTH AND DEVELOPMENT OF FISH LARVAE - Simangunsong, Tohap; Anjaini, Jefri; Soedibya, Petrus Hary Tjahja; Liu, Chun-Hung (Journal of Environmental Engineering and Sustainable Technology, 2024)
Fish farming has become essential in meeting the global demand for animal protein, with the maintenance of fish larvae being a crucial stage in determining production success. Tubifex worms, rich in essential nutrients, have long been used as natural feed in aquaculture. This article provides a comprehensive review of the utilization of Tubifex worms, covering their morphological and anatomical characteristics, habitat, and nutritional content. The benefits of using Tubifex worms as natural feed include enhanced growth and health of fish larvae and cost efficiency in production. This article also outlines feeding procedures, risk management, and challenges in the mass production of Tubifex worms. Additionally, recent research and practical approaches that can be implemented to optimize the use of Tubifex worms in fish farming are discussed, providing guidance for fish farmers and researchers in aquaculture.